Pengaruh Penggunaan Media Permainan Kartu Huruf Terhadap Kemampuan Membaca Siswa Kelas I SDN 13 Sitiung Kabupaten Dharmasraya - Widyaningsih Ningsih; Amar Salahuddin; Faradilla Intan Sari (Jurnal Dharma PGSD, 2021)
This research is motivated by learning Indonesian Babasa which is still not optimal.  The learning process has not used interesting media. Therefore, many student learning outcomes are below the minimum completeness criteria.  For this reason, researchers conducted a study using letter card game media.  The purpose of this study was to determine the effect of letter card game media on student learning outcomes in Indonesian language theme 8 Natural Events I SDN 13 Sitnung. This type of research is a pre experimental design.  The research design is a one group pretest-posttest design.  The population in this study were all first grade students of SD Negeri 13 Sitiung, Dhamasraya Regency. The sample in this study was taken using a sampling technique or saturated sample. Data collection techniques were taken by giving pre-test and post-test. The sample in this study amounted to 27 students. The study was conducted in  SD Negeri 13 Sitiung When this research was conducted in the second semester of the 2020/2021 Academic Year, it was adjusted to the learn ing schedule. Based on the results of the paired samples t test, a significance of 0.000 <0.05 was obtained. It can be concluded that there is an influence of letter card game media on student learning outcomes for Indonesian language theme 8 Natural Events in class I SDN 13 Sitiung.  give a very good influence on students' Indonesian learning outcomes.  Media card game letters can be used by teachers to relate subject matter to the real world of students, make students active and can improve student learning outcomes.